The argumentative written skills through the use of the pedagogical mediation of Facebook as an educational network. A reflection on the state of art - Rodríguez Sánchez, Guillermo Augusto; Torres Ortiz, Jaime Andrés (Escribanía, 2018)
The present report is a review of the state of the art relating to the researchesthat have been conducted in the last three years, about the perspectivesin written argumentation procedures through the pedagogical use of Facebookas an educational network.Some comments and considerations have been drawn with regard to theuse of the social networks in the school education, having as a starting pointthe students of “Rural Technical Education Institution”. The current social network is the only one used at the secondary school level. On that social network the students interact sharing personal and social experiences that keep up a continuous connectivity and a recurrent presence of it. Given these conditions it is possible to suggest that Facebook might be maximized as an educational tool toward the strengthening of the written argumentative skills, characterized by the exchange of languages, enrichment of views and the diversification the discussions as well as the language skills.